2016
DOI: 10.1063/1.4952730
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and electroluminescent characterization of nanometric multilayers of SiOX/SiOY obtained by LPCVD including non-normal emission

Abstract: This work describes the analysis and fabrication by Low Pressure Chemical Vapor Deposition of two light-emitting capacitors (LECs) constituted by nanometric multilayers of silicon-rich oxide. For both structures, seven layers were used: three light emitting layers with 6% silicon excess and four conductive layers with 12% silicon excess for one LEC and the other with 14% silicon excess. Both LECs were annealed at 1100 °C. Both multilayers demonstrate a substantially improved photoluminescent response compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Table 2 summarizes the Si-nc features of M-LECs. this regimen for the subsequent measurements, as previously reported in [39] and agreeing with others works [34,40]. During first current-voltage measurement, Si-ncs are ordered forming conductive trajectories (electroforming) whereby electrons can be easily driven through the SRO multilayers [22,23].…”
Section: Figure 5(a)supporting
confidence: 88%
See 1 more Smart Citation
“…Table 2 summarizes the Si-nc features of M-LECs. this regimen for the subsequent measurements, as previously reported in [39] and agreeing with others works [34,40]. During first current-voltage measurement, Si-ncs are ordered forming conductive trajectories (electroforming) whereby electrons can be easily driven through the SRO multilayers [22,23].…”
Section: Figure 5(a)supporting
confidence: 88%
“…Across their conductive path, they can impact other electrons not only increasing the current density but also augmenting the number of electrons able to decay at different trap levels, enhancing the emission intensity as well. In [39], it is reported that thermionic emission, Poole-Frenkel, trap-assisted tunneling, and impact ionization conduction mechanisms are responsible for the charge transport. The first two dominate conduction in low (E < 2 MV/cm) and medium (2 MV/cm < E < 4 MV/cm) electric field regimes, respectively.…”
Section: Figure 5(a)mentioning
confidence: 99%
“…The emission of visible light in nanostructured oxides (applicable to optoelectronic devices) [ 1 , 2 , 3 ], light absorption effects such as the so-called down conversion effect (solar cells) [ 4 , 5 ], and resistive switching (non-volatile memories of multiple states) [ 6 , 7 , 8 , 9 ] are some of the characteristics that make SiO x a material that needs to be studied deeply, also taking into account that silicon is the second most abundant material on our planet. Another favorable feature that this material provides is that it can be obtained using multiple synthesis techniques [ 10 , 11 , 12 , 13 , 14 ]. Among these techniques, it has been found that the technique of chemical vapor deposition activated using a hot filament (HFCVD) offers important characteristics due to the ease of obtaining thin films and powders with diverse electrical and optical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several reports of the behavior of this material using various techniques [ 10 , 11 , 12 , 13 , 14 , 15 ], in this investigation the spectroscopic and compositional behavior of SiO x films are analyzed, where the material is obtained using the HFCVD technique with a short deposition time of 3 min. This material is suitable for large-scale applications and may be important for future applications, such as light absorbing devices (photosensors and solar cells), as well as for light emitting devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SRO films have been considered as promising candidates for potential applications in Si-based optoelectronic devices, and their fully compatibility with the complementary metal-oxide-semiconductor (CMOS) processes. At present, different techniques or methods have been employed to produce SRO films or SRO/SiO 2 MLs [6][7][8][9][10][11][12][13]. In such structures, the SRO-thickness, Si-excess and annealing temperature are parameters that promote the formation of Si-NCs and radiative defects, affecting the optical and electrical properties of SRO monolayers or SRO/SiO 2 ML.…”
Section: Introductionmentioning
confidence: 99%